Exiting the captaverse: Digital resistance and its limits pre and post the Covid-19 pandemic - Szakolczai, Janos Mark (Criminology & criminal justice, 2025)
The term ‘data’, ubiquitous in the Digital Age, etymologically refers to a piece of information ‘given’ (datum). In this article, I argue that the term ‘capta’ would be more accurate, since information is often taken from us. Capturing information replicates normative elements of abuse, surveillance, control and harm becoming central and problematic within the emergence of the ‘onlife’. I illustrate my argument via an ethnomethodological consideration of my attempt to resist the unwilling capture of personal information. Since 2016, I have engaged in what I call an ‘offlife’ existence, phasing out all devices and platforms that covertly capture personal data. However, my experiment has proven problematic, impractical and has even been perceived as being anti-social, especially in light of the Covid-19 pandemic. In the conclusion of this article, I consider the problematics of engaging in some form of resistance to data collection.